Intracoronary transplantation of pluripotent stem cell-derived cardiomyocytes: Inefficient procedure for cardiac regeneration. (January 2023) - Kobayashi, Hideki; Tohyama, Shugo; Kanazawa, Hideaki; Ichimura, Hajime; Chino, Shuji; Tanaka, Yuki; Suzuki, Yota; Zhao, Jian; Shiba, Naoko; Kadota, Shin; Narita, Kazumasa; Naito, Takafumi; et al.
Abstract: Advances in stem cell biology have facilitated cardiac regeneration, and many animal studies and several initial clinical trials have been conducted using human pluripotent stem cell-derived cardiomyocytes (PSC-CMs). Most preclinical and clinical studies have typically transplanted PSC-CMs via the following two distinct approaches: direct intramyocardial injection or epicardial delivery of engineered heart tissue. Both approaches present common disadvantages, including a mandatory thoracotomy and poor engraftment. Furthermore, a standard transplantation approach has yet to be established. In this study, we tested the feasibility of performing intracoronary administration of PSC-CMs based on a commonly used method of transplanting somatic stem cells. Six male cynomolgus monkeys underwent intracoronary administration of dispersed human PSC-CMs or PSC-CM aggregates, which are called cardiac spheroids, with multiple cell dosages. The recipient animals were sacrificed at 4 weeks post-transplantation for histological analysis. Intracoronary administration of dispersed human PSC-CMs in the cynomolgus monkeys did not lead to coronary embolism or graft survival. Although the transplanted cardiac spheroids became partially engrafted, they also induced scar formation due to cardiac ischemic injury. Cardiac engraftment and scar formation were reasonably consistent with the spheroid size or cell dosage. These findings indicate that intracoronary transplantation of PSC-CMs is an inefficient therapeutic approach. Graphical abstract: Unlabelled Image Highlights: We tested the feasibility of intracoronary administration of PSC-CMs in primates. This study is the first to show PSC-CM spheroids engrafted via coronary injection. PSC-CM spheroids induced substantial scar formation due to coronary embolism. Dispersed human iPSC-CMs resulted in neither coronary embolism nor graft survival. Intracoronary injection of PSC-CMs was an inefficient approach for cardiac repair.